Women's Economic Empowerment Through Sharia Micro-Finance Institutions In Indonesia: A Qualitative Research - Nawawi, Zuhrinal M; Soemitra, Andri; Dalimunthe, Mahfuzah (Ekonomi Syariah IAIN Kudus, 2022)
Women's empowerment has become an agenda that has recently been put forward and has become one of the essential agendas in sustainable development. One of the common problems women micro-enterprises face is the difficulty of accessing sources of capital. Islamic microfinance institutions are an alternative that can be utilized by women micro-enterprises in Indonesia to overcome the challenges in accessing business capital. This research uses a qualitative approach to study literature and in-depth interviews. The literature study was conducted by selecting relevant papers by accessing the Google Scholar database using the keywords “women empowerment” AND “Islamic microfinance” OR “Islamic microfinance”. The search time range is limited to the last 5 years, namely 2017 to 2022. The literature search results found 19 relevant papers. 4 sharia microfinance institutions are reported to run women's empowerment programs, namely sharia cooperatives, Baitul Mal Wat Tamwil, Zakat Management Organizations, and Micro Waqf Banks. The results of interviews with 20 lecturers of Islamic Economics strengthen the role of Islamic microfinance institutions in women's empowerment programs in Indonesia.